Corporation's Criminal Liability in Indonesia: A Response to the Weak Enforcement of Corporate Social Responsibility - Syukri Kurniawan; Hari Sutra Disemadi (University of Jember, 2020)
Corporate Social Responsibility (CSR) is a corporate commitment to contribute to sustainable economic development by focusing on the balance between attention to economic, social, and environmental aspects. This paper argues that corporations are subject to criminal law, which can be subject to criminal liability if they do not carry out CSR obligations. This study aims to find out the linkage of sanctions arrangements and the urgency of regulations on criminal liability if the corporation does not carry out CSR obligations. In practice, CSR is only based on corporate awareness and commitment. In the meantime, CSR enforcement's most basic weakness is the absence of strict sanctions for corporations that deny CSR, especially in terms of criminal sanctions. Instead, the sanction is limited to administrative as set out in Act No. 25/2007 on Investment, with a lack of legislation governing criminal sanctions against CSR prevention. In so doing, there is a need to introduce sanctions against corporations that deny CSR, by taking into account adverse impacts to the environment and community. KEYWORDS: Corporate Social Responsibility, Criminal Liability, Corporations.